Requirements to the students in humanistic educational environment - Elena A. Maksimova (Saratov State University, 2021)
The purpose of the research presented in the article is to reveal the dependence of the changes in the requirements to students on the level of the development of the society. Its topicality is connected with the necessity to match the requirements to the students in the educational process and the character of professional tasks that would be solved by them in the future. The tasks, in their turn, are determined by the concept of labour in the intellectual labour society. The key characteristics of the activity-competence basis of professional activity are shown. It is supposed that the number of people involved in intellectual labour will continue to grow. Hence, it is emphasized that specialists working under such conditions should be ready for multifunction, for rotation, for improving their qualification. An example of transprofessional education aimed at achieving this goal is supplied. The main stages of its organization in foreign colleges are enumerated. The practical aspect of the problem of actualization of the requirements to the students can be fulfilled step by step. It begins with the professional orientation of the senior form students through motivating them to develop critical thinking, to master information processing methods, to get experience in command projecting. In the period of professional education in higher educational establishments it continues as formation of universal and general cultural competence of would-be specialists of different spheres of activity.